Report of the Fortieth Regular Meeting of the Executive Committee - Executive Committee (EC) (2020)
The fortieth Regular Meeting of the Executive Committee of the Inter-American Institute for Cooperation on Agriculture (IICA) was held in accordance with the provisions contained in the Rules of Procedure of the Executive Committee. The 2019 Executive Committee comprised the following Member States: Bahamas, Brazil, Canada, Chile, Costa Rica, Honduras, Panama, Peru, St. Kitts and Nevis, St. Vincent and the Grenadines, Uruguay and Venezuela.